A reliable assay for ensuring the biological activity of anti T lymphocyte immunoglobulin as an alternate to compendial flow cytometry method. (May 2020) - Chand, Subhash; Vaish, Utpreksha; Sharma, Anu; Mishra, Nripendra Nath; Prasad, Jai Prakash; Mahajan, Richi V.
Abstract: The assay of Anti T lymphocyte immunoglobulin for final drug product testing is carried out using flow cytometry on Peripheral Blood Mononuclear Cells (PBMCs) as specified in European and British Pharmacopeia. An alternate assay was developed wherein the potency based quality control evaluation of Anti T lymphocyte immunoglobulin is carried out by measuring complement dependent cytotoxicity (CDC) using fluorescent resazurin dye. The reported bioassay was specific, linear (R 2  = 0.98), precise (%GCV for repeatability was 3.54% and intermediate precision was 4.27%) and accurate with relative bias of −5.54%. On the basis of results obtained from the repeated performances on single available product, system suitability criteria and sample acceptance criteria were proposed wherein Slope from 4 PL curve fit results for Reference Standard (RS) should be > 0.9, EC50 for RS should lie between 0.264 and 1.131 μg/ml and fold response should be > 2. Confidence interval range and estimated relative potency range obtained from the method validation were narrower than those mentioned for compendial method.